Relationship between ecological indicators and soil properties (in case of a wetland) - Szalai, Zoltán; Szabó, Mária; Zboray, Nóra; Kiss, Klaudia; Horváth-Szabó, Kata; Jakab, Gergely; Balázs, Réka; Németh, Tibor; Madarász, Balázs (Hungarian Geographical Bulletin, 2012)
Ecological indicators have been defined for higher plants. In theory with the use of these indicator values we can make predictions for the abiotic environmental factors based on cenological analysis. There are only few publications which have focused on validation of the published indicators. The scale dependence of these indices is poorly studied too. Present paper focuses on applicability of soil related ecological indicators in small scale studies. Three soil related indices were studied along a hydromorph toposequence, such as Simon’s W, R and Soó’s N values. Simon ’s T value also was applied to compare applicability soil related ecological indicators with non-soil related ones for small areas. These values were determined on the basis of cenological measurement and compared with soil physical and chemical properties. Our results suggest that W values can be use only for small scale ecological indications.